Análisis de sustitución o complementariedad laboral entre migrantes y no migrantes en el Ecuador en los años 2003 y 2012 - Caraguay Guamán, Jenny Paulina (2014)
Internal migration in Ecuador has been one modifiers of the population structure therefore in the present investigation analyzes labor substitution or complementarity between migrants and non-migrants examining whether there is competition between the two groups. Is reviewed the Economic theory respect to migration and the National Survey on Employment, Unemployment and Underemployment ENEMDU Conducted by the National Institute of Statistics and Census (INEC) order to apply an least-squares ordinary model to see how migration affects the employment rate. Results obtained indicated that internal migration in Ecuador has characteristics of labor complementarity; migrants and non-migrants complement each other, discovering that some of the activities rejected by non-migrants are accepted by migrants, especially low-skilled activities; non-migrants are not willing to accept low wages and let these jobs are filled by migrants